Prenatal screening of gestation. Clinical aspects and management of pregnancy. - Chávez Espinoza, Fermín (2015)
It points out that the prevention and control involves prenatal education for women from adolescence, to have a comprehensive orientation physical, mental and socially preparing for pregnancy. Emphasis is placed on early diagnosis, using the anamnesis, clinical examination and laboratory. Periodic monitoring at different parameters, particularly fetal growth, blood pressure, weight, proteinuria, etc. Advice on the first visit and subsequent controls; hygienic dietary regime. Considerations duration of pregnancy and fetal maturity. Prematurity and growth retardation. Post-term pregnancy and maturity. Bleeding of the first or second half of pregnancy. Fetal abnormalities and heritage. Similarly, consideration of hemolytic disease of the newborn, hypertension in pregnancy. Finally, considerations on high-risk pregnancy, physiological aspects of pregnancy and labor induction.